Drivers of Healthy Lifestyle Behaviors among Arable Crop Farmers: Evidence from Kwara State, Nigeria - Adebisi, Oluwaremilekun; Muhammad-Lawal, Abdulazeez; Adebisi, Luke Oloruntoba (Jordan Journal of Agricultural Sciences, 2024)
Globally, a healthy lifestyle is important in maintaining the balance between man and the environment as well as the prevention and avoidance of Non-Communicable Diseases (NCDs) especially among rural dwellers in developing economies where the state of quality healthcare is in chaos. In theory, individuals are products of investments made in their health which are either health-promoting or health-damaging behavior. We causally identify the motives of healthy lifestyle practices among arable crop farmers in Kwara state, Nigeria using a cross-sectional survey. We found out that less than average of the arable crop farmers sampled practiced healthy lifestyles and the factors that strongly influenced the healthy lifestyle behavior of arable crop farmers were gender, age, education, farm size, farm income as well as distance to healthcare. A policy simulation illustrates that taking consideration of the socioeconomic characteristics that drive the practice of healthy lifestyles will improve the health status of the populace, especially the rural dwellers, and also avoid lifestyle-related diseases in the future.